A velocity map imaging study of multiphoton photodissociation and photoionisation dynamics in niobium oxide, NbO - Köckert, H; Gentleman, AS; Pickering, J; Mackenzie, SR (Taylor and Francis, 2020)
Velocity map imaging has transformed our capabilities in terms of determining photofragmentation and photoionisation thresholds. Here, we present an investigation into the multi-photon dissociation and photoionisation dynamics of niobium monoxide (NbO) probed using velocity-map imaging via the C 4Σ– ← X 4Σ– and B 4Π ← X 4Σ- transitions. Analysis of the kinetic energy release spectra permits determination of refined values of the dissociation energies for NbO and NbO+ of 60,650 ± 124 and 57,414 ± 124 cm−1, respectively, in good agreement with previous values using other methods. With the same instrument, we have further recorded photoelectron images which exhibit a long progression assigned to the production of the ground state, X 3Σ− NbO+ (v +), for which a vibrational constant of 1002 ± 11 cm−1 is determined.